Selective Cytotoxicity of Dihydroorotate Dehydrogenase Inhibitors to Human Cancer Cells Under Hypoxia and Nutrient-Deprived Conditions - Miyazaki, Yukiko; Inaoka, Daniel K.; Shiba, Tomoo; Saimoto, Hiroyuki; Sakura, Takaya; Amalia, Eri; Kido, Yasutoshi; Sakai, Chika; Nakamura, Mari; Moore, Anthony L.; Harada, Shigeharu; Kita, Kiyoshi (Frontiers in Pharmacology, 2018)
Human dihydroorotate dehydrogenase (HsDHODH) is a key enzyme of pyrimidine de novo biosynthesis pathway. It is located on the mitochondrial inner membrane and contributes to the respiratory chain by shuttling electrons to the ubiquinone pool. We have discovered ascofuranone (1), a natural compound produced by Acremonium sclerotigenum, and its derivatives are a potent class of HsDHODH inhibitors. We conducted a structure–activity relationship study and have identified functional groups of 1 that are essential for the inhibition of HsDHODH enzymatic activity. Furthermore, the binding mode of 1 and its derivatives to HsDHODH was demonstrated by co-crystallographic analysis and we show that these inhibitors bind at the ubiquinone binding site. In addition, the cytotoxicities of 1 and its potent derivatives 7, 8, and 9 were studied using human cultured cancer cells. Interestingly, they showed selective and strong cytotoxicity to cancer cells cultured under microenvironment (hypoxia and nutrient-deprived) conditions. The selectivity ratio of 8 under this microenvironment show the most potent inhibition which was over 1000-fold higher compared to that under normal culture condition. Our studies suggest that under microenvironment conditions, cancer cells heavily depend on the pyrimidine de novo biosynthesis pathway. We also provide the first evidence that 1 and its derivatives are potential lead candidates for drug development which target the HsDHODH of cancer cells living under a tumor microenvironment.